عورت کا حق ِحضانت اور شریعتِ اسلامیہ ایک تحقیقی مطالعہ - Shahida Parveen (Pakistan Journal of Islamic Research)
Islam has shown more concern to marital issues because this relationship provides sound and stable ground in upbringing of human being. If this bond is broken, our religion commands to safeguard children therefore women have more right to custody of children than men, in principle custody belongs to because they are more compassionate and more kind, they know better the related art, better and they are more patient in dealing with the difficulties involved. The mother has the more right to custody of her child whether boy or girl, as long as she does not re-marry. Welfare of the minor should be considered in every situation. The conditions of custody are: being accountable (i.e., an adult of sound mind etc.), being free (as opposed to being a slave), being of good character, being a Muslim if t  he child concerned is a Muslim, and being able to fulfill all obligations towards the child. The mother should not be married to a person who is a stranger (i.e., not related) to the child. If one of these conditions is not fulfilled and there is an impediment such as insanity or having remarried, etc., the woman forfeits the right to custody, but if that impediment is removed, then the right to custody is restored. This paper will analyze these issues in Islamic and contemporary  perspective.